2016
DOI: 10.5194/se-7-727-2016
|View full text |Cite
|
Sign up to set email alerts
|

Development of a numerical workflow based on <i>μ</i>-CT imaging for the determination of capillary pressure–saturation-specific interfacial area relationship in 2-phase flow pore-scale porous-media systems: a case study on Heletz sandstone

Abstract: Abstract. In this case study, we present the implementation of a finite element method (FEM)-based numerical porescale model that is able to track and quantify the propagating fluid-fluid interfacial area on highly complex microcomputed tomography (µ-CT)-obtained geometries. Special focus is drawn to the relationship between reservoir-specific capillary pressure (p c ), wetting phase saturation (S w ) and interfacial area (a wn ). The basis of this approach is highresolution µ-CT images representing the geomet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Equation 12 is the effective stress acting upon the grain particles of the porous granular material, for which σ s , γ wa , and the PDF of the grain particles can be determined by experimental methods (e.g., digital image analysis, X-ray computed tomography, mercury intrusion porosimetry, etc. ; Brusseau et al, 2006;Peche et al, 2016;Tatomir et al, 2016). There still are 𝑢 w , 𝑢 a , G w (R), G a (R), and h(R) left unknown, usually, 𝑢 w and 𝑢 a can be described by matric suction (Zhang & Lu, 2020).…”
Section: Theoretical Conceptmentioning
confidence: 99%
“…Equation 12 is the effective stress acting upon the grain particles of the porous granular material, for which σ s , γ wa , and the PDF of the grain particles can be determined by experimental methods (e.g., digital image analysis, X-ray computed tomography, mercury intrusion porosimetry, etc. ; Brusseau et al, 2006;Peche et al, 2016;Tatomir et al, 2016). There still are 𝑢 w , 𝑢 a , G w (R), G a (R), and h(R) left unknown, usually, 𝑢 w and 𝑢 a can be described by matric suction (Zhang & Lu, 2020).…”
Section: Theoretical Conceptmentioning
confidence: 99%
“…Experimental data could then be generated for the true capillary pressure, saturation, and fluid-fluid interfacial area for a large number of states accurately and precisely under equilibrium conditions with the results interpreted in an inclusive and robust manner. These conditions have been compromised in certain respects in virtually all studies (Chan & Govindaraju, 2011;Chen et al, 2007;Joekar-Niasar & Hassanizadeh, 2012;Karadimitriou et al, 2014;Peche et al, 2016). In effective experiments, the need exists for high-resolution imaging that requires extended periods of time to capture the range of media considered, the size of the systems investigated, the number of states that can be observed, the time allowed for equilibrium to be achieved, and in many cases the monitoring of interfacial curvature needed to compute the true capillary pressure.…”
Section: Role Of Interfacial Areamentioning
confidence: 99%
“…Many attempts conclude that the HG hypothesis is appropriate and helpful, although some have concluded that only a reduction in hysteretic behavior can be achieved by including interfacial area in the relation (Cheng et al, 2004;Held & Celia, 2001;Joekar-Niasar, Prodanovic, et al, 2010;Karadimitriou et al, 2014;Porter et al, 2009). The issue is considered open and work has continued over recent years using consistently improving methods (Godinez-Brizuela et al, 2017;Nikooee et al, 2016;Paustian, 2018;Peche et al, 2016;Sivanesapillai et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental methods were proposed to measure the fluid–fluid interfacial areas (FIFAs): interface partitioning tracer test (IPTT), where the tracer is dissolved in an aqueous (Anwar et al., 2000; Brusseau et al., 2007; Kim et al., 1997; Saripalli et al., 1997) or in a gaseous (Costanza‐Robinson & Brusseau, 2002; Kim et al., 1999) phase, high‐resolution industrial X‐ray microtomography (XMT), and synchrotron XMT (Araujo & Brusseau, 2020; Brusseau et al., 2008; Culligan et al., 2006; McDonald et al., 2016; Narter & Brusseau, 2010; Patmonoaji et al., 2018; Peche et al., 2016; Porter et al., 2010; Ying et al., 2017), the gas adsorption chemical reaction (Ying et al., 2017), experiments using microfluidic devices (Karadimitriou et al., 2016), and the kinetic interface sensitive tracer method (Tatomir et al., 2018). The experimental methods for measuring the FIFA are usually applied in controlled laboratory conditions, that is, tracer methods, XMT, micro models (e.g., Dobson et al., 2006; Karadimitriou et al., 2016; McDonald et al., 2016; Porter et al., 2010; Tatomir et al., 2018), but also in the field, that is, tracer methods (Annable et al., 1998; Nelson & Brusseau, 1996; Simon & Brusseau, 2007).…”
Section: Introductionmentioning
confidence: 99%